2005
DOI: 10.1111/j.1651-2227.2005.tb01975.x
|View full text |Cite
|
Sign up to set email alerts
|

Maternal perception of excess weight in children: A survey conducted by paediatricians in the province of Milan

Abstract: Objective: To establish whether maternal perception of a child's body weight (BW) and food intake is related to the level of maternal education. Study design: Height and BW of 569 mother/child couples were measured, and mothers received a questionnaire regarding their perception of their own weight and their child's BW and food intake. Results: Twenty‐nine percent of mothers and 35% of children were overweight or obese. Only 10% of the mothers underestimated their own weight, while 37% overestimated it. In con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
18
2
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(24 citation statements)
references
References 22 publications
3
18
2
1
Order By: Relevance
“…In contrast with earlier reports suggesting that heavier mothers are less likely to recognize overweight (Maynard et al 2003;Adams et al 2005;Parkinson et al 2011), and that higher maternal education is associated with better recognition of offspring overweight (Baughcum et al 2000;Chang & Christakis 2003;Genovesi et al 2005;Manios et al 2009), this study suggests that poor judgement among contemporary parents is unrelated to maternal weight or any sociodemographic measures. Reasons for poor weight awareness might include denial, a reluctance to admit to a weight problem, or desensitization to weight excess in a society where overweight has is rapidly becoming the norm.…”
Section: Discussioncontrasting
confidence: 99%
“…In contrast with earlier reports suggesting that heavier mothers are less likely to recognize overweight (Maynard et al 2003;Adams et al 2005;Parkinson et al 2011), and that higher maternal education is associated with better recognition of offspring overweight (Baughcum et al 2000;Chang & Christakis 2003;Genovesi et al 2005;Manios et al 2009), this study suggests that poor judgement among contemporary parents is unrelated to maternal weight or any sociodemographic measures. Reasons for poor weight awareness might include denial, a reluctance to admit to a weight problem, or desensitization to weight excess in a society where overweight has is rapidly becoming the norm.…”
Section: Discussioncontrasting
confidence: 99%
“…Both themes may also reflect a general lack of understanding of the degree of health risk associated with childhood obesity that is independent of lifestyle factors. This finding is consistent with past work in other countries, although published work has largely been reported only for pre-school children ( 25 , 26 ) . Parents of overweight children commonly show bias in believing their children to be more active and eating a healthier diet than healthy-weight children ( 27 ) , and extrapolate from this that paediatric growth charts are not relevant for their child ( 25 , 28 ) .…”
Section: Discussionsupporting
confidence: 93%
“…Possible explanations for the discrepancies between studies may be due to differences in the age-range of included children, the BMI cut-off criteria to define overweight, reference frame for overweight, the size of the study population, and choices of conducted subgroup analyses [16,17,20]. In contrast to the findings in our 2009 dataset, several groups found that parents with low SES are more likely to underestimate their child's weight status [25,41,43,49], although Jansen and Brug reported that SES is not associated with the parent's awareness of their child's weight status [16,22]. In contrast to these studies we found that the parents with a high level of education were more likely to underestimate their child's weight status.…”
Section: Comparison With Other Literaturecontrasting
confidence: 65%